UN common country assessment update for the Philippines - Navarro, Adoracion M.,Reyes, Celia M.,Francisco, Kris A. (Philippine Institute for Development Studies, 2021)
This common country assessment update for the Philippines underpins the sustainable development partnership framework for the Philippines and the United Nations (UN). Taking off from the analysis of the national baseline on sustainable development goals (SDGs) and progress in the SDGs, this report employs UN's approach of framing the sustainable development outcomes under three pillars, namely, people, prosperity and planet, and peace. The report dissects the coronavirus disease (COVID-19) impacts and trajectories of the sustainable development outcomes under each pillar. COVID-19 impacts are anticipated to result in a regression in human development capacities and opportunities. These are also expected to thwart economic prosperity, change consumption behavior, and affect the environment. Delays in peacekeeping activities and fiscal resources realignments might also affect the communities that are trying to recover from violence and armed conflicts, especially in Mindanao. To mitigate further regression in development, the report recommends the following, among others: for the people pillar, governance improvements in areas such as social welfare programs delivery to vulnerable groups; for the prosperity and planet pillar, science-based policy strategies that will consider the current problems exposed by the pandemic, as well as incorporate the timeliness of the policy responses; and for the peace pillar, the continued cooperation between the national government and the Bangsamoro government in ensuring that the recently gained peace dividends are protected and stakeholders do not slide back on their commitments.
10419/241054
Keywords: Graue Literatur; COVID-19; SDGs; human development; prosperity and planet; peace